2016
DOI: 10.1371/journal.pone.0164294
|View full text |Cite
|
Sign up to set email alerts
|

The Seagrass Effect Turned Upside Down Changes the Prospective of Sea Urchin Survival and Landscape Implications

Abstract: Habitat structure plays an important mediating role in predator-prey interactions. However the effects are strongly dependent on regional predator pools, which can drive predation risk in habitats with very similar structure in opposite directions. In the Mediterranean Sea predation on juvenile sea urchins is commonly known to be regulated by seagrass structure. In this study we test whether the possibility for juvenile Paracentrotus lividus to be predated changes in relation to the fragmentation of the seagra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 61 publications
2
16
0
Order By: Relevance
“…Both between-species and species-seascape interactions can be considered as an emergent property of the heterogeneity due to the spatial configuration of the landscape (Didham, 2010). For example, meadow proximity influences the trajectory of free-ranging bison moving in a patchy forest landscape (Dancose, Fortin, & Xulin, 2011), corridors of vegetation showing low-resistance to movement ease the spread of mountain pine beetles (Powell et al, 2018), while the spatial arrangement of seagrass affected the predation on sea urchins (Farina et al, 2016). Our models included variables describing the spatial configuration of both the seascape and the artificial blocks (Table 2), however the limited spatial extent of our study or the abundance of cells containing boulders (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both between-species and species-seascape interactions can be considered as an emergent property of the heterogeneity due to the spatial configuration of the landscape (Didham, 2010). For example, meadow proximity influences the trajectory of free-ranging bison moving in a patchy forest landscape (Dancose, Fortin, & Xulin, 2011), corridors of vegetation showing low-resistance to movement ease the spread of mountain pine beetles (Powell et al, 2018), while the spatial arrangement of seagrass affected the predation on sea urchins (Farina et al, 2016). Our models included variables describing the spatial configuration of both the seascape and the artificial blocks (Table 2), however the limited spatial extent of our study or the abundance of cells containing boulders (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Despite an overall lack of seascape maps of proper resolution and the inability to track animals compared to their terrestrial counterpart, marine ecologists are increasingly considering the spatially explicit seascape configuration to better resolve the mechanisms underlying the ecological processes. For example, predation risk for Mediterranean sea urchin Paracentrotus lividus and predator identity emerged as a function of the arrangement of seagrass patches (Farina et al, 2016). Aerial imagery in clear tropical water systems allowed to show that grazing pressure on macroalgae decreases with the distance from the nearest coral reef providing shelter to fish (Gil, Zill, & Ponciano, 2017; Madin, Madin, & Booth, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Farina et al (2009Farina et al ( , 2014 found high proportions of middle-sized sea urchins in patchy meadows in accordance with the efficient shelter that Posidonia oceanica leaves provide from the visual mechanism of predatory fish. However, the three-dimensional structure of large seagrass meadows can become a 'death trap' in the presence of high densities of bottom predators (Farina et al, 2014(Farina et al, , 2016Schmidt & Kuijper, 2015). For example, Sector 5, in the Gulf of Oristano, is PeerJ reviewing PDF | (2020:03:47281:2:0:NEW 3 Sep 2020)…”
Section: Manuscript To Be Reviewedmentioning
confidence: 99%
“…), which is known as effective predators of sea urchins (e.g. Farina et al, 2016) and whose proliferation is probably favoured by the bio-deposits that accumulate beneath the nearby mussel farms (Inglis & Gust, 2003).…”
Section: Manuscript To Be Reviewedmentioning
confidence: 99%
“…These species move relatively freely across the seascape, and are critical agents for sea urchin population control (Guidetti et al, 2004;Hereu, Zabala, Linares, & Sala, 2005). While other bottom-associated species also prey on urchins, their effect on urchin populations is relatively minor (Sala & Zabala, 1996; but see Farina et al, 2016).…”
Section: Introductionmentioning
confidence: 99%